Update on Fundamental Mechanisms of Thyroid Cancer - Prete, Alessandro; Borges de Souza, Patricia; Censi, Simona; Muzza, Marina; Nucci, Nicole; Sponziello, Marialuisa (Frontiers in Endocrinology, 2020)
The incidence of thyroid cancer (TC) has increased worldwide over the past four decades. TC is divided into three main histological types: differentiated (papillary and follicular TC), undifferentiated (poorly differentiated and anaplastic TC), and medullary TC, arising from thyroid C cells. This review discusses the molecular mechanisms associated to the pathogenesis of different types of TC and their clinical relevance. In the last years, progresses in the genetic characterization of TC have provided molecular markers for diagnosis, risk stratification and treatment targets. Recently, papillary thyroid cancer has been reclassified into two molecular subtypes, named BRAF-like and RAS-like, associated to different range of cancer risks. Similarly, the genetic characterization of follicular thyroid cancer has been proposed to complement the new histopathological classification in order to estimate the prognosis. New analyses characterized a comprehensive molecular profile of medullary thyroid cancer raising the role of RET mutations. More recent evidences suggested that immune microenvironment associated to TC may play a critical role in tumor invasion, with potential immunotherapeutic implications in advanced and metastatic TC. Several types of ancillary approaches have been developed to improve the diagnostic value of fine needle aspiration biopsies in indeterminate thyroid nodules. Finally, liquid biopsy, as non-invasive diagnostic tool for body fluids genotyping, brings a new prospective of disease and therapy monitoring. Despite all these novelties, much work still remains to be done to fully understand the pathogenesis and biological behaviors of the different types of TC and to transfer this knowledge in clinical practice.